Praktik Habituasi Lokal dalam Mitigasi Kesiapsigaan Banjir di Desa Jombok, Kecamatan Kesamben, Kabupaten Jombang - Abu Tazid; Wardhani, Galuh Rachma (Universitas Sunan Drajat Lamongan, Indonesia, 2025)
Flooding is a natural disaster that frequently strikes Jombok Village, Kesamben District, Jombang Regency. This event encourages residents to continuously adapt by building collective habits passed down from repeatition generation to generation. The method used in this study is phenomenology qualitative with data collection through in-depth interviews, observation, and document collection. The findings of the study indicate that the community has developed a habitus in facing floods based on community behaviors such as moving items to higher ground, building temporary embankments, checking embankments, removing trash on the embankment that blocks it, and implementing a simple evacuation system based on mutual cooperation as a form of local habituation. Mitigation still uses this adaptation method, which is still reactive and has not been organized into a more comprehensive